ANALISIS PENGARUH PROFITABILITAS, KEBIJAKAN DEVIDEN, KEBIJAKAN UTANG, DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009 – 2011) - Ika Fanindya Jusriani; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2013)
Investors should be cautious in determining investment decisions because if any, investors not only have nothing to gain but all initial capital in investment also be lost. Therefore, investors need to gather complete and accurate information about the company to be chosen as a place for investment. This study investigated the influence of profitability, dividend policy, debt policy, and managerial ownership on firm value.The data used in this study is a secondary data, namely manufacturing go public company's annual report in 2009 - 2011, especially listed in the Indonesia Stock Exchange (www.idx.co.id). The sample used a total of 136 companies with information concerning cash dividend. Data processing method used is analyse descriptive, classical assumption test, multiple regression analysis, the coefficient of determination test, f test and t test. The results showed that the profitability and dividend policy has a significant impact on firm value with a positive direction. As for the debt policy and managerial ownership has no significant effect on firm value.